Organizational design: Culture and incentives - Kets, W (University of Oxford, 2021)
Why do some organizations perform so much better than others, and often persistently so? While the economics literature traditionally emphasizes the importance of incentives, other social sciences focus on the role of organizational culture. Yet very little is known about how an organization's incentive structure and its culture jointly shapes its performance. This paper therefore develops a formal model of how an organization's incentives and culture interact. The model offers a unified explanation for a variety of empirical phenomena, including why an organization's culture can be difficult to change and why there can be persistent performance differences across companies even when they have access to the same technology and resources.